Data Dissemination Protocol for Mobile Sink in Wireless Sensor Networks. (27th April 2014) - Sharma, Suraj; Jena, Sanjay Kumar
Abstract : In wireless sensor networks, the sensor nodes find the route towards the sink to transmit the data. The sensor node transmits the data directly to the sink, or it relays the data through neighbor nodes. The nodes near to the sink transmit more data than other nodes. It results in the small lifetime of the network. To prolong the lifetime of the network, we use the mobile sink approach. The mobile sink makes the network dynamic. It is a challenging task to find the route in the dynamic network. In this paper, we have proposed a distributed tree-based data dissemination (TEDD) protocol with mobile sink. The protocol is validated through simulation and compared with the existing protocols using some metrics such as energy consumption, average end-to-end delay, and throughput. The experiment results show that the proposed protocol outperforms the existing protocols.